STRATEGI PENGEMBANGAN TANAMAN BUNGA KANTONG SEMAR (Nepenthes) DI DESA KOTO TINGGI, KECAMATAN RAMBAH ( Studi Kasus Yagiza Nursery ) - -, Mudiaris (Jurnal Mahasiswa Prodi Manajemen Fakultas Ekonomi, 2015)
This study aims to determine the internal and external factors affecting the business development of flowering plantsNepenthes Mr. Multazam (yagiza nursery) Koto Tinggi Village District of Rambah, formulate alternative strategies that can beapplied in developing the business and determine the priority strategies that can be applied in business development offlowering plants Nepenthes Mr. Multazam (yagiza nursery) Koto Tinggi Village District of Rambah. Sampling was carried outin the development effort of flowering plants Nepenthes Mr. Multazam (yagiza nursery) in the Koto Tinggi village Rambah ofDistrict. Data used are primary and secondary data. Data analysis method used is the analysis of business. SWOT analysis toformulate alternative strategies and Matrix QSP to determine strategic priorities. From the research, the priority strategiesthat can be applied in the development of flower plants Nepenthes Mr. Multazam (yagiza nursery) Koto Tinggi Village Districtof Rambah is Leveraging existing infrastructure and increase cooperation with the government of the total amount gainedattraction 5,501